First-trimester placental vascular development in multiparous women differs from that in nulliparous women. (17th January 2018) - Ballering, Gea; Leijnse, Janneke; Eijkelkamp, Niels; Peeters, Louis; de Heus, Roel
Abstract: Objective: Multiparas differ from nulliparas by delivering larger babies with larger placentas and by having a lower risk of developing placental syndromes. We postulate that these differences result from a different initial course of placental vascular development. Study design: We measured placental flow index (FI), vascularization index (VI) and placental volume by 3D power Doppler and obtained blood samples at 8, 10 and 12 weeks pregnancy in 34 healthy nulliparous and 16 multiparous women with an uneventful pregnancy. Results: Between 8 and 12 weeks multiparas differed from nulliparas in a more rapid initial rise in FI, a higher angiopoietin-2 (ang2) level at eight weeks and no decline in the VEGF/sVEGF-R ratio. Nevertheless, at 12 weeks the FI and placental volume were indistinguishable between both study groups. Conclusions: These results combining serially measured placental vascularization, placental volume and circulating angiogenetic factors show initial differences in placental development, that howeve, did not maintain till the end of first trimester. The results support the concept that early placental vascular development differs between nulliparas and multiparas. Nevertheless, it is unclear whether these differences contribute to the development later on in pregnancy of intergroup differences in birthweight and incidence of placental syndromes.